ADOPTION OF DIGITAL TECHNOLOGIES IN THE HIGHER EDUCATION - Abdukadirova Xalida Abduxamedovna; Mukumova Nargis Nuriddinovna (PT ANTIS INTERNATIONAL PUBLISHER, 2026)
Objective: This article examines the digital transformation of higher education institutions and their impact on the development of distance education. It analyzes modern approaches to defining the concepts of